2007
DOI: 10.1111/j.1365-2133.2006.07636.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-affinity nerve growth factor receptor inhibitors on symptoms in the NC/Nga mouse atopic dermatitis model

Abstract: We suggest that NGF plays an important role in the pathogenesis of atopic dermatitis-like skin lesions via the high-affinity NGF receptor. These findings provide a new potential therapeutic approach for the amelioration of symptoms of atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 46 publications
(56 reference statements)
0
39
0
Order By: Relevance
“…52) Similarly, application of the TrkA antagonists AG879 and K252a to the nape of atopic nc/nga mice significantly improved established dermatitis and scratching behavior and reduced the numbers of nerve fibers in the epidermis, suggesting the importance of nGf in the pathogenesis of atopic dermatitis-like skin lesions. 53) thus, nGf and its receptors may be among the antipruritic targets in pruritic skin diseases such as atopic dermatitis.…”
Section: Anti-ngf Antibody and Ngf Receptor Antagonistsmentioning
confidence: 99%
“…52) Similarly, application of the TrkA antagonists AG879 and K252a to the nape of atopic nc/nga mice significantly improved established dermatitis and scratching behavior and reduced the numbers of nerve fibers in the epidermis, suggesting the importance of nGf in the pathogenesis of atopic dermatitis-like skin lesions. 53) thus, nGf and its receptors may be among the antipruritic targets in pruritic skin diseases such as atopic dermatitis.…”
Section: Anti-ngf Antibody and Ngf Receptor Antagonistsmentioning
confidence: 99%
“…This is likely due to the increased levels of NGF and PGP9.5 in mite-infested Cftr DF508/DF508 mice because treatment of Cftr DF508/DF508 mice with K252a, a high-affinity NGF receptor inhibitor that is also shown to dampen PGP9.5 expression via NGF suppression, 8 significantly inhibited the scratching behavior in mite-infested Cftr DF508/DF508 mice. Although we cannot exclude the possibility of occurrence of increased levels of NGF and PGP9.5 in mite-free Cftr DF508/DF508 mice, our results propose that CFTR dysfunction may correlate with neurite outgrowth in/into epidermis accompanied with NGF hyperproduction in mice kept together with mite-infested NC/Nga mice.…”
Section: Discussionmentioning
confidence: 99%
“…6 It has been demonstrated that nerve growth factor (NGF) plays roles in the pathogenesis of itch and itch-induced skin lesions using skin-lesioned NC/Nga mice, an animal model for human AD, and that inhibiting the physiological effects and production of NGF prevents these symptoms. 7,8 Furthermore, AD patients with itch showed significant gains in NGF plasma levels compared to controls, and a correlation was noted between plasma NGF and severity of symptoms. 9 Thus, NGF plays a role in the regulation of susceptibility to itch reaction and skin lesions.…”
mentioning
confidence: 94%
“…In fact, high-affinity NGF-receptor inhibitors, AG879 and K252a, are effective in improving the established dermatitis (50) and scratching behavior in the NC/Nga atopic dermatitis model mouse (51), and anti-NGF antibody is also effective in inhibiting epidermal innervation and scratching in NC/Nga mouse (52). However, complete interception of NGF signaling may cause some side effects because autocrined NGF is thought to be involved in keratinocyte proliferation and important for normal elongation of neuronal fibers.…”
Section: Discussionmentioning
confidence: 99%